Smallholder oil palm farmer: peasant sensibilities and production style in Southeastern Chiapas - Cano Castellanos, Ingreet Juliet (2023)
Based on ethnographic research in Southeastern Chiapas, this article addresses the cultural production between rural groups and agribusiness companies linked to oil palm monoculture. The notions peasant sensibilities and production style are proposed to explore the signs and meanings that mediate power relations and interactions on the ground. The article argues that when local groups identify themselves as smallholders they affirm their belonging to the regional rural society, while companies use the category of smallholder to locate socio-culturally those who occupy the first link in the productive chain. However, this category not only obscures regional and local dynamics of social differentiation, but also the different ways in which companies value the resources and labor extracted from the territory. In this unequal social scenario, it is possible to appreciate that the peasant sensibilities do not correspond to a class culture, nor to a collective identity, but to an eclectic and subaltern practical and communicative sensibility that smallholders appeal to in order to challenge their adverse incorporation into this plantation system and to try to achieve certain margins of maneuver. Nevertheless, when these margins are put at risk due to disadvantageous circumstances, the social differences that traverse these peasant sensibilities hamper strong social cohesion. In this scenario, while waiting for better circumstances, smallholders cope with the production styles of companies depending on their different ecological, economic, cultural, and political conditions.